The Role of Outcome Mapping in Developing a Rural Telemedicine System - Tucker, William; Blake, Edwin (University of the Western Cape, 2008)
We describe the use of Outcome Mapping to guide the design of a rural telemedicine consultation system in South Africa. While Outcome Mappin g was not primarily intended to guide design, we show that it tied in well with a cyclical participatory design method for an Information an d Communication Technology for Development project